International Oil Conference and Exhibition in Mexico 2007
DOI: 10.2118/108643-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of Acoustic Waves for Reservoir Stimulation

Abstract: Research related to weak elastic wave stimulation of oil reservoirs started in the late 1950's. Activity peaked in the 1970's and 1980's in the US and in the Soviet Union. However in recent years there has been a resurgent interest and research. This interest derives form observations made in some fields near areas affected by earthquakes and, even heavy traffic, where changes in water level and oil production have been observed. For example, some variations in oil production were noticed in Kern County during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Low-frequency vibration production technology could improve the oil recovery through the follow mechanisms (Cidoncha 2007;Ariadji 2005;Kurawle et al 2009): (1) reducing the capillary forces and fine particles blocking rate inner pore throats could increase the absolute permeability of rocks; (2) crude oil viscosity decrease, hydrophilicity increase on rock surface, and an additional drive force added by vibration could improve the fluid seepage rate; (3) velocity difference between solid and fluid might increase crude oil detachment or extraction in bypassed throats, so as to reduce residual oil saturation and improve oil recovery. Thereby, the real pore volume under wave is only part of the whole pores.…”
Section: Introductionmentioning
confidence: 99%
“…Low-frequency vibration production technology could improve the oil recovery through the follow mechanisms (Cidoncha 2007;Ariadji 2005;Kurawle et al 2009): (1) reducing the capillary forces and fine particles blocking rate inner pore throats could increase the absolute permeability of rocks; (2) crude oil viscosity decrease, hydrophilicity increase on rock surface, and an additional drive force added by vibration could improve the fluid seepage rate; (3) velocity difference between solid and fluid might increase crude oil detachment or extraction in bypassed throats, so as to reduce residual oil saturation and improve oil recovery. Thereby, the real pore volume under wave is only part of the whole pores.…”
Section: Introductionmentioning
confidence: 99%
“…Further field studies have shown that in order to achieve a high success in method implemenation in complicated mining and geological wells operating conditions it is necessary to conduct theoretical, laboratory and field studies, design and technological research (Gil Cidoncha, 2007, Kostrov et al, 2008.…”
Section: The History Of the Eorm Application Using Vibrowave Impactmentioning
confidence: 99%
“…In a radius of 5-6 meters from the well several branched cracks are formed without closing after the the pressure is removed, that is why there is no need for consolidation of sand unlike the hydraulic fracturing. In the oil fields of Texas in 1958, the fracturing method known as vibrofrac has been successfully applied for the first time (Gil Cidoncha, 2007, Kostrov et al, 2008, Westermark et al, 2001. The essence of the method is to create harmonic shock waves in BFZ due to special placement of charges.…”
Section: The History Of the Eorm Application Using Vibrowave Impactmentioning
confidence: 99%
“…This method is called (artificial) seismic production technology or lowfrequency vibration oil extraction technology (Cidoncha 2007;Kurawle et al 2009), which has been tested in many oil fields with certain effects, including increase in injection rate, production rate improvement, and plugging removal. When the technology is used, two processes are involved because of the fluid-solid coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive experimental studies on the influence of lowfrequency vibration have been conducted by Nikolaevskiy et al (1996), Dusseault et al (2000), Ariadji (2005), Wang et al (2005), Cidoncha (2007), and Liu et al (2012) in terms of the following factors: whole permeability, O/W relative permeability, capillary force, residual oil saturation, connate water saturation, oil viscosity, porosity, and O/W separation. Nevertheless, fewer studies on dynamic model building and mathematic analysis are conducted than on the experimental method.…”
Section: Introductionmentioning
confidence: 99%